T4 rather than TSH correlates with BMD among euthyroid adults - Sheng, Ning; Xing, Fei; Wang, Jie; Duan, Xin; Xiang, Zhou (Frontiers in Endocrinology, 2023)
Abstract Purpose: The objective of this study was to evaluate the association between thyroid hormone and bone mineral density (BMD) among euthyroid adults. Methods: This cross-sectional study researched the information from the National Health and Nutrition Examination Survey 2007-2010. We included 3759 euthyroid participants finally. We used multivariate linear regression models to evaluate the linear relationship between the thyroid hormone profile and BMD. Subgroup analyses stratified by gender and age were further performed. Moreover, the nonlinear relationship was characterized by fitted smoothing curves and generalized additive models, and Logistic regression models were used to determine the association of TSH and T4 with previous fractures. Results: The weighted multivariable linear regression models showed no association between TSH and BMD. FT4, T4, FT3 and T3 were negatively associated with the total femur BMD and the total spine BMD after adjusting all covariates. Subgroup analyses demonstrated that all groups had a negative association between T4 and BMD, even in patients with osteopenia/osteoporosis. The nonlinear relationship characterized by smooth curve fittings and generalized additive models suggested that an obvious U-shaped, an inverted U – shaped and an L - shaped curve was exhibited between thyroid hormone with BMD in different subgroups. In addition, normal high-level T4 was associated with an increased prevalence of previous fractures than normal low-level T4. Conclusions: In this sample of euthyroid adults, T4 exhibits a negative correlation with BMD, regardless of age and gender, both in subjects with normal and lowered BMD. Moreover, high-normal FT4 was associated with an increased prevalence of previous fractures. TSH was not associated with variations of BMD and the fracture risk.